2014
DOI: 10.2174/1871520614666140723114217
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Inhibits VEGF/VEGFR2, PI3K/Akt and MAPK Signaling Cascades in the Hamster Cheek Pouch Carcinogenesis Model

Abstract: Ellagic acid offers promise as a lead compound for anticancer therapeutics by virtue of its ability to inhibit key oncogenic signaling cascades and HDACs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…p38-phosphorylation. VEGF/VEGFR signaling pathway has been confirmed to play central roles in pathological angiogenesis, and binding of VEGFR2 with VEGF can activate numerous downstream signal pathways, including Akt and p38, which sequentially promote endothelial cell growth, migration and tube formation (32)(33)(34). Therefore, we further evaluated whether these signaling pathways are involved in the PC-3 CM AM -induced vasculogenesis of BM-EPCs.…”
Section: Pc-3 CM Am Induces Activation Of Vegfr2- Akt-andmentioning
confidence: 98%
“…p38-phosphorylation. VEGF/VEGFR signaling pathway has been confirmed to play central roles in pathological angiogenesis, and binding of VEGFR2 with VEGF can activate numerous downstream signal pathways, including Akt and p38, which sequentially promote endothelial cell growth, migration and tube formation (32)(33)(34). Therefore, we further evaluated whether these signaling pathways are involved in the PC-3 CM AM -induced vasculogenesis of BM-EPCs.…”
Section: Pc-3 CM Am Induces Activation Of Vegfr2- Akt-andmentioning
confidence: 98%
“…AKT and MAPK pathways, which play important roles in promoting cell growth and survival, are often abnormally activated in melanoma cells through N-RAS, BRAF and PTEN mutations (Jakob et al, 2012;Luo & Shen, 2017;Zebary et al, 2013). Moreover, other studies indicated that EA is related to the modulation of the AKT and MAPK signaling networks (Kowshik et al, 2014;Umesalma, Nagendraprabhu, & Sudhandiran, 2015). Also, EA increases p53 protein levels in some cancer cell lines (Li et al, 2005).…”
Section: Ellagic Acid Attenuates Akt and Mapk Signaling Pathways Anmentioning
confidence: 99%
“…In the resistant ovarian subcell line A2780CisR, pretreatment with EA for 48 hr could enhance the cytotoxicity of cisplatin resulting in the prevention of cisplatin resistance development . Furthermore, a hamster model with oral oncogenesis was developed to investigate the antiangiogenic effect of EA, which was mediated via the abrogation of hypoxia driven MAPK, VEGF/VEGFR2, and phosphoinositide‐3‐kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathways involving the suppression of HIF‐1α and HDAC6 response . Interestingly, EA was applied to combine with other natural products or anticancer drugs with the aim of potentiating their anticancer effects, including curcumin, quercetin, embelin, and 5‐fluorouracil (5‐FU) .…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%